2022
DOI: 10.14348/molcells.2022.5015
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Safety of Mesenchymal Stem Cell-Based Ex Vivo Therapy Using Herpes Simplex Virus Thymidine Kinase

Abstract: Human mesenchymal stem cells (MSCs) are multipotent stem cells that have been intensively studied as therapeutic tools for a variety of disorders. To enhance the efficacy of MSCs, therapeutic genes are introduced using retroviral and lentiviral vectors. However, serious adverse events (SAEs) such as tumorigenesis can be induced by insertional mutagenesis. We generated lentiviral vectors encoding the wild-type herpes simplex virus thymidine kinase (HSV-TK) gene and a gene containing a point mutation that result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 62 publications
1
4
0
Order By: Relevance
“…Histological sections of the paraffin‐embedded heart, liver, spleen, lungs, and kidneys were stained with hematoxylin and eosin (HE) for light microscopy evaluation (Figure 10I). The HE imaging results were all normal, and there was no tumorigenesis (uncontrolled cell proliferation) of the engineered transplanted cells, as mentioned in the literature 25 …”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…Histological sections of the paraffin‐embedded heart, liver, spleen, lungs, and kidneys were stained with hematoxylin and eosin (HE) for light microscopy evaluation (Figure 10I). The HE imaging results were all normal, and there was no tumorigenesis (uncontrolled cell proliferation) of the engineered transplanted cells, as mentioned in the literature 25 …”
Section: Resultssupporting
confidence: 65%
“…The HE imaging results were all normal, and there was no tumorigenesis (uncontrolled cell proliferation) of the engineered transplanted cells, as mentioned in the literature. 25 …”
Section: Resultsmentioning
confidence: 99%
“…Mesodermal differentiation was carried out as described previously ( 18 ). Briefly, for adipogenic and osteogenic differentiations, naïve MSCs and MSCs/CD cells were plated at a density of 5×10 4 in a 24-well plate and allowed to grow to confluence.…”
Section: Methodsmentioning
confidence: 99%
“…Another study demonstrated the antitumor effect of MSCs obtained from adipose tissue (AT-MSC) transduced with the HSV-tk gene for the treatment of glioblastoma derived from the U87 cell line [3]. These results show that MSCs, regardless of their origin, are good carriers of suicide genes for glioblastoma gene therapy [55][56][57][58][59].…”
Section: Oncolytic Virus Deliverymentioning
confidence: 99%